2008
DOI: 10.1007/s10552-008-9111-3
|View full text |Cite
|
Sign up to set email alerts
|

Vegetables- and antioxidant-related nutrients, genetic susceptibility, and non-Hodgkin lymphoma risk

Abstract: Genetic susceptibility to DNA oxidation, carcinogen metabolism, and altered DNA repair may increase non-Hodgkin lymphoma (NHL) risk, whereas vegetables-and antioxidant-related nutrients may decrease risk. We evaluated the interaction of a priori-defined dietary factors with 28 polymorphisms in these metabolic pathways. Incident cases (n = 1,141) were identified during 1998-2000 from four cancer registries and frequency-matched to population-based controls (n = 949). We estimated diet-gene joint effects using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Our finding of inverse associations between the intake of green leafy vegetables and cruciferous vegetables and the risk of NHL is in general agreement with previous studies [3,5,18]. The National Cancer Institute Surveillance, Epidemiology, and End Results population-based, case-control study [5,9], in which the same food frequency questionnaire was used, also reported an inverse association for NHL overall with the intake of cruciferous (OR = 0.62, CI = 0.39-1.00) and green leafy vegetables (OR = 0.59, CI = 0.36-0.96). However, a recent report from the Iowa Women's Health Study [11] found a statistically significant inverse association for NHL overall with the intake of all fruit and vegetables (RR = 0.69; CI = 0.51-0.94) and yellow/orange vegetables (RR = 0.72; CI = 0.54-0.97), but not green leafy vegetables or cruciferous vegetables.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding of inverse associations between the intake of green leafy vegetables and cruciferous vegetables and the risk of NHL is in general agreement with previous studies [3,5,18]. The National Cancer Institute Surveillance, Epidemiology, and End Results population-based, case-control study [5,9], in which the same food frequency questionnaire was used, also reported an inverse association for NHL overall with the intake of cruciferous (OR = 0.62, CI = 0.39-1.00) and green leafy vegetables (OR = 0.59, CI = 0.36-0.96). However, a recent report from the Iowa Women's Health Study [11] found a statistically significant inverse association for NHL overall with the intake of all fruit and vegetables (RR = 0.69; CI = 0.51-0.94) and yellow/orange vegetables (RR = 0.72; CI = 0.54-0.97), but not green leafy vegetables or cruciferous vegetables.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, the dietary intake of fruit and vegetables has received great attention in the prevention of NHL because antioxidants and other constituents in these foods are thought to influence immune function and to inhibit oxidative processes involved in carcinogenesis and cell proliferation [1,2]. The possible link between NHL and the intake of fruit, vegetables, and the constituents in these foods has been examined in several epidemiologic studies [3][4][5][6][7][8][9][10][11]. Some studies have reported inverse associations between the risk of NHL and a higher intake of all vegetables combined [5,12], green leafy vegetables [3,5,13], or cruciferous vegetables [5], but others have found no associations [4,6,7,11] or even a suggestive positive association with green leafy vegetables [7].…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between the intake of vegetables and genetic polymorphisms in pathways involved in oxidative stress, DNA repair, and carcinogen metabolism in relation to NHL risk may influence the results of individual studies, in particular those with null findings, [22][23][24][25][26] and warrant further examination. 39,40 Despite our lack of a priori hypothesis and the limited evidence of heterogeneity across common NHL subtypes examined in our analysis, the finding of significant risk estimates primarily confined to DLBCL agrees with several previous reports. [12][13][14]23,24 However, inverse associations with dietary intake of carotenoids have been reported for other NHL subtypes.…”
Section: Discussionsupporting
confidence: 91%
“…Due to the known differences between dietary intake and circulating levels of tocopherols in non-deficient individuals, the current results cannot be simply compared to past case-control and cohort studies that evaluated linear associations between dietary and/or supplement intake of tocopherols and NHL risk (1012, 14, 15, 37). The findings from previous dietary assessment studies have been inconsistent with three case-control studies reporting inverse associations between tocopherol intakes and NHL risk (1012), whereas a case-control study and two cohort studies reported no association for dietary and supplement intake (1315).…”
Section: Discussionmentioning
confidence: 99%